Causes and Consequences of Emigration in Chagunarayan Municipality of Bhaktapur District - Rijal, Nirajan (Nepalese Journal of Development and Rural Studies, 2022)
Large proportion of the Nepalese citizens are emigrating from own country in search of better employment opportunities and prosperity. The study aims to assess causes and consequences of emigration particularly in Changunarayan Municipality of Bhaktapur district. The study employed case study research design followed by quantitative and qualitative approaches of data collection. The required data are collected from randomly selected 50 HHs residing in four settlements (i.e. Chagunarayan, Jhaukhel, Duwakot and Chhaling) of the municipality ward number four. This study found that unemployment, difficulties in transportation, attraction towards foreign countries, perverting other people from neighbor, disrespect to owns' occupation, wanting to earn more are the major causes of emigration. The emigrants are enjoying in the destinations with various facilities and they are able to improve the living standard of their family members and prosperity. The emigrants' household members get an opportunity to spend a considerable portion of their family income in child education, health treatment and also for buying land property. The availability of communication facilities, adjustments in native people's way of life and achieving better social status have been noted as other positive outcomes of the emigration. However, emigration of youth people also has negatively affected social and cultural structures in the study area. The festivals are compelled to celebrating by less active group member in the community with less enjoyment and excitement. Even the returned migrate people are not giving interest in the social and cultural and religious festivals. This might be reason that most people have feeling that one should develop the own area rather than migrating to other areas. Therefore, local government need to become responsive and responsible in addressing the negative consequences of emigration as far as possible.